LESBIAN, GAY, BISEKSUAL, DAN TRANSGENDER (LGBT) DAN HAK ASASI MANUSIA (HAM) - Yeni Sri Lestari (Jurnal Community, 2018)
AbstractThe success of one country's democratic system is characterized by the increasing subsistence of freedoms owned by citizens such as freedom of expression, association to other individual freedoms as stated in the respective constitutions of a country. Notwithstanding the Universal Declaration of Human Rights (DUHAM), policies on human rights began to thrive in the world as the main pillar of democracy, one of which speaks of the recognition of LGBT rights. LGBT phenomena that hit most of the world are often viewed from two contradictory perspectives, those who legalize and which do not legalize (illegal). This study found that although both the United States and Indonesia share the principles of democracy in the life of the state, the Muslim majority of Indonesia views LGBT as a violation of Islamic values and norms, but the recognition of human rights is still appreciated only by the behavior of LGBT as an act of social aberrations. Keyword: LGBT, HAM, Amerika dan Indonesia